The contemporary of modernist school of thought in reading the Quranic text: A critical analysis of al-Jaliy Fi al Tafsir by Abu Yaarob al-Marzouqi / Ashraf Fouly Youssef Mohamed Elassal - Ashraf Fouly Youssef , Mohamed Elassal (2019)

(untitled)
Nowadays, modernism is taking dimensions and trends affecting and overwhelming our Islamic thoughts and heritage. It has become in the minds of its adherents an ambiguity that must be clarified, as it is harm and evil to be prevented. There is a necessity to stop fierce intellectual attacks having been done by Arab writers and intellectuals who have overlooked the heritage. These intellectuals have ignored the Exegesis of the Qur'an without knowledge or reliance on language, knowledge of the sources, origins and principles of Islam. This research is important as it is an attempt to clarify how pure the Holy Qur’an is from any modernist philosophical and orientalist attempts targeting either the sanctity of the Qur’an or giving a chance to any other theories that manipulate the Exegesis of the Qur’an out of the intended context that Allah wants to convey. “Clear Exegesis” written by Abu Yaarob al-Marzouqi is the latest modern philosophical Exegeses of the Quranic text, The objectives of the researcher, depending on the critical analytical method, are: 1- to identify the latest developments of the Modernist School in reading the Quranic Text, 2- to illustrate whether the Modernist School is a renewable one and 3- whether the Modernist School uses modern methods? The researcher came out with several results the most prominent of which are first illustrating gradual plans for reading the Quranic Text in the modernist ideology from the beginning until its last image by Abu Yaarob al-Marzouqi. The study concludes that this book is not worthy being classified as one of the philosophical Exegeses. This is due two reasons: 1- the author’s lack of Islamic and scientific standards, and 2- the Book is only a modernist philosophical project chosen to support and prove some Quranic verses and Suras that are interpreted according to the modernist ideology and philosopher’s mind. One of the research findings is that al-Marzouqi believes that legislation and the process of legislating legislation are a right of unanimous unanimity (for all members of the Ummah) without mediation from scholars, which is a consensus that can never be imagined. It is just a way of persuasion used to get rid of the Ummah’s scholars (the spiritual tyrants) . The study revealed the most important developments of modernist ideology through the Exegesis of al Marzouqi, the most important of which are: 1- he did not deny the revelation, but considered it a kind of creativity, and 2- he did not deny Sunnah but considered it a kind of human diligence, he did not claim that the stories of the prophets and miracles are superstitions, but he symbolizes and keeps them away from truth. He did not divine the individual mind like others preceding him. He, however, divines the collective mind and makes it above Islamic Legislation. The most important thing recommended by the researcher is that students and researchers alike should address in their research the latest developments of Modernist and Orientalist schools in order to expose their plans so as not to pass their destructive ideology to the minds of our youth and thus destroy our religion in the name of the religion.